The KGB (Russian Secret Police): Its composition, aims and methods - Graser, H.G. (Scientia Militaria - South African Journal of Military Studies, 2012)
Any discussion of the Russian Secret Police, or KGB (’Committee for State Security’) must of necessity be preceded by a brief outline of the USSR’s true political set-up. There are two primary governing bodies in the Soviet Union: one is the Supreme Soviet and its Presidium - the other the Communist Party and its Central Committee and Politburo. Put into their proper perspective, this emerges: the Supreme Soviet, which appoints Ministerial staff and runs the USSR’s ’government’, is in fact no more than a rubber stamping body of men who see to it that the decisions of the Communist Party are duly ratified and implemented. To ensure that its directives are properly adhered to, and to prevent counter-revolutionary activity against the Party, the KGB controls the USSR security apparatus.